2019
DOI: 10.1080/0284186x.2018.1546059
|View full text |Cite
|
Sign up to set email alerts
|

Association between oropharyngeal cancers with known HPV and p16 status and cervical intraepithelial neoplasia: a Danish population-based study

Abstract: Background: Persistent infection with high-risk genotypes of human papillomavirus (HPV) is the main risk factor in the development of uterine cervical precancerous lesions and cervical cancer (CC), and cases of HPV-induced oropharyngeal squamous cell carcinoma (OPSCC) is increasing in the Western world. We investigated the association between HPV and p16 status and previous results of cervical examinations, including cytological and histological tests, in females with OPSCC. Material and Methods: We included f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 29 publications
(35 reference statements)
1
15
0
1
Order By: Relevance
“…Some studies investigated smaller retrospective cohorts of women with OPSCC to identify their risk of CC [[22], [23], [24], [25]]. However, some lacked p16 status [22,25], while others stratified their data based on p16 status when available [23,24]. Skinner et al [22] studied a mixed small cohort of men and women (n = 143) with multiple potentially HPV-related cancers at different sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies investigated smaller retrospective cohorts of women with OPSCC to identify their risk of CC [[22], [23], [24], [25]]. However, some lacked p16 status [22,25], while others stratified their data based on p16 status when available [23,24]. Skinner et al [22] studied a mixed small cohort of men and women (n = 143) with multiple potentially HPV-related cancers at different sites.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Danish study [23] found no difference in the association between HPV/p16+ve OPSCC and CC. However, they identified 1.35 greater odds of developing HPV/p16+ve OPSCC in women with high grade squamous cell abnormalities or CC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Acta Oncologica, Christensen et al report the results of an interesting Danish study aiming to further elucidate the potential association between cervical abnormalities and subsequent HPV-related OPSCC [16]. The authors included all female OPSCC patients in Eastern Denmark during 2000-2014 (n = 417) and determined the HPV and p16 status of the tumours.…”
mentioning
confidence: 99%
“…Smoking is a well-known risk factor for both cervical cancer and OPSCC [3]. The data of Christensen et al [16] indicate that the association between HPV status in OPSCC and history of cervical abnormalities may be more pronounced in smokers than in non-smokers. However, the statistical power was limited, and larger studies are needed to further disentangle the impact of smoking on risk of OPSCC in women with previous highgrade CIN. In summary, some studies suggest that women with a history of cervical premalignancies are at increased risk of OPSCC [9,10] and also non-cervical anogenital cancers [10,12,13,17].…”
mentioning
confidence: 99%